Pengaruh Kemudahan Penggunaan, Persepsi Manfaat, dan Promosi Penjualan Terhadap Keputusan Pembelian Tiket Bioskop Pada Aplikasi TIX.ID - Winda Sefhiani; Winarto (Journal Of Accounting and Business, 2024)
This study aims to determine the effect of ease of use, perceived usefulness and sales promotion on cinema ticket purchase decisions on TIX.ID application. The approach used in this study is an associative approach. The population in this study were users of cinema ticket applications Online TIX.ID at Cinema XX1 Transmart Rungkut Surabaya City. The number of samples in this study was 100 respondents. The sampling technique is carried out using the non-probability method and the number of samples is calculated using the Slovin formula. The data analysis technique used in this study is multiple linear regression analysis using SPSS software version 25.0. The results of this study show that the Ease of Use Variable (X1) partially has a positive and significant effect on the purchase decision (Y) of cinema tickets on the TIX.ID application. the variable of perceived usefulness (X2) partially has a positive and significant effect on the purchase decision (Y) of cinema tickets on the TIX.ID application. The sales promotion variable (X3) partially has a positive and significant effect on the purchase decision (Y) of cinema tickets on the TIX.ID application.  The variables ease of use (X1), perceived usefulness (X2) and sales promotion (X3) together (simultaneously) have a significant effect on purchasing decisions (Y) cinema tickets on TIX.ID application.